A Simple Technique to Estimate the Flammability Index of Moroccan Forest Fuels - M'Hamed Hachmi; Abdessadek Sesbou; Hassan Benjelloun; Nesrine El Handouz; Fadoua Bouanane (Journal of Combustion)
A formula to estimate forest fuel flammability index (FI) is proposed, integrating three species flammability parameters: time to ignition, time of combustion, and flame height. Thirty-one (31) Moroccan tree and shrub species were tested within a wide range of fuel moisture contents. Six species flammability classes were identified. An ANOVA of the FI-values was performed and analyzed using four different sample sizes of 12, 24, 36, and 50 flammability tests. Fuel humidity content is inversely correlated to the FI-value, and the linear model appears to be the most adequate equation that may predict the hypothetical threshold-point of humidity of extinction. Most of the Moroccan forest fuels studied are classified as moderately flammable to flammable species based on their average humidity content, calculated for the summer period from July to September.